PENERAPAN OPERATION COSTING DAN KAITANNYA DENGAN KEAKURATAN PENETAPAN HARGA JUAL (Case Study at PT X — A Finishing Company in Printing Industries in Bandung) - Paulina Permatasari; Hendra Setiadi (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Pricing Decision is influenced by several factors, Le: cost, competitor and customer. In pricing decision process, it's really important for companies to be able to accurately calculate its product costs so that the profile of product profitability could be figured. Many methods are available to be used in calculating product costs. One of the methods is Operation costing method, which is a hybrid costing system that is applied to batch of similar but not identic products. Operation costing is a combination of process costing and job-order costing methods. Operation costing assigns direct material cost to the products using job-order costing method and conversion cost assigned using process costing method. With the application of operation costing at this finishing company, the cost assignment process to the products could be more accurate and also the pricing decision.